Efek Penambahan Virgin Coconut Oil (VCO) terhadap Perkembangan Jengger dan Bobot Testis Ayam (Gallus sp.) - Santoso, Mohammad Sigit; Tana, Silvana; Mardiati, Siti Muflichatun (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2010)
Chicken is one of food sources that useful for human as a source of animal’s protein. Chicken has to produce good quality of meat and egg. One way to increase the product of chick is through the management of chicken food by adding Virgin Coconut Oil (VCO). The advantage of VCO is known as a safe product for human, therefore it will be safe for chicken too, there no doubt to consume the meat.The purpose of this research is to know about the effect of VCO related to the development of comb and testis weight. The sample of this research are 20 leghorn rooster. The method of this research is random sampling with four treatment and five repetition (Po: 0 cc/kg, P1 : 1,5 cc/kg, P2 : 3 cc/kg, and P3 : 6 cc/kg). The data is obtained by using ANOVA with 95% significance. The result of data showed that there are not real different about the development of comb and testis weight’s chicken. It shows that the concentration of using VCO as additif feed to increase the productivity not successful yet.